Interleukin-6-to-albumin ratio for mortality prediction in critically ill elderly patients - Yang, Lim Kai (2024)
The association between interleukin-6 (IL-6) and serum albumin with mortality in critically ill elderly patients, jointly interpreted as a ratio, has been scarcely reported. This thesis aimed to investigate the prognostic value of IL-6- to-albumin ratio in this special population. This was a cross-sectional study conducted in the mixed ICU of two university-affiliated hospitals in Malaysia. Consecutive elderly patients (aged ≥60 years) admitted to the ICU who underwent simultaneous measurement of plasma IL-6 and serum albumin were recruited. The prognostic value of IL-6-to-albumin ratio was assessed by analysis of the receiver-operating characteristic curve. A total of 112 critically ill elderly patients were recruited. The outcome of all-cause ICU mortality was 22.3%. The calculated IL-6-to-albumin ratio was significantly higher in the non-survivors compared to the survivors (14.1 [IQR, 6.5-26.7] versus 2.5[IQR, 0.6-9.2] pg/mL, P <0.001]. The area under the curve of IL- 6-to-albumin ratio for discrimination of ICU-mortality was 0.766 (95% CI, 0.667- 0.865, P <0.001) which was slightly higher than that of IL-6 and albumin alone, but statistically insignificant. After adjusting for severity of illness, the IL-6-to-albumin ratio remained as an independent predictor of ICU-mortality with adjusted odd ratio of 3.278 (95% CI, 1.382-7.770, P = 0.007). Comparison of the ratio with the APACHE II or SOFA score did not show its superiority. Also, additions of the ratio to the APACHE II or SOFA score did not significantly improve the prognostic ability of the scores. In conclusion, a high IL-6-to-albumin ratio is independently associated with ICU-mortality in critically ill elderly patients, but our findings did not suggest that it is superior to the standalone IL-6, APACHE II, or SOFA score.